The Morphological Connotations of the Linked taa in the Dictionary of Diwan Al-Adab by Al-Farabi (d. 350 AH) - Mamdooh , Fayhaa (Islamic Sciences Journal, 2023)
The major point of this research is the semantics of the tied ta’ in the singular noun and its morphological connotations in one of the dictionaries of the Arabic language, which is the dictionary (Diwan al-Adab) by al-Farabi, which was specialized and concerned with the weights of the words. The morphology of the ta' connected in this foreign language, and what Al-Farabi added to it in terms of connotations. As for the first part, it includes the significance of the ‘taa’ on the differentiation between the noun of gender and its singular form number, and the significance of the ‘taa’ on privacy, its indication of compensation, and its indication of confirming femininity. While the second part includes the indication of the taa on the number of the masculine, and its indication of exaggeration. Its indication of the abundance of the thing in the place, and its indication of Nominative verb form are also presented as well.